2017
DOI: 10.1089/ten.teb.2016.0370
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Bone Regeneration: A Systematic Review and Meta-Analysis of Animal Studies

Abstract: These findings prove that DM type 1 negatively influences bone formation compared with a healthy condition, irrespective of the bone substitute material used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
0
27
1
1
Order By: Relevance
“…Moreover, our study included a three to five times larger proportion of patients with diabetes than other studies (Table ). Diabetes was associated with a very poor prospect of healing in our study, and accumulated evidence from animal studies suggests that bone regeneration is strongly reduced in animals with diabetes . Taken together, these differences probably explain why the overall healing rate in our study was lower than others’.…”
Section: Discussioncontrasting
confidence: 59%
“…Moreover, our study included a three to five times larger proportion of patients with diabetes than other studies (Table ). Diabetes was associated with a very poor prospect of healing in our study, and accumulated evidence from animal studies suggests that bone regeneration is strongly reduced in animals with diabetes . Taken together, these differences probably explain why the overall healing rate in our study was lower than others’.…”
Section: Discussioncontrasting
confidence: 59%
“…In our review process it has been identified some studies evaluating the success of bone regeneration techniques in DM animals (2230), however, there were few regarding DM in humans despite the safety of performing implant therapy in such condition having been proven. Studies in non-controlled DM patients are even scarcer, probably due to the previously mentioned complications and ethical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, all experiments should be performed in a similar manner, but as previously observed in other systematic reviews using pre-clinical studies, this is difficult to achieve. 3,158,159 Another limitation of the systematic review is the low quality of reporting in pre-clinical papers. Study blinding was seldom reported and randomization was reported in less than half of the included papers.…”
Section: Limitations Of the Study And Clinical Relevancementioning
confidence: 99%
“…Bone is one of the most commonly transplanted tissues with over 2 million bone graft procedures performed annually worldwide. 1 However, bone regeneration is still a challenge for large defects or in patients with systemic diseases that negatively affect bone regeneration (e.g., osteoporosis 2 or diabetes mellitus 3 ). Autografts, i.e.…”
Section: Introductionmentioning
confidence: 99%